From self-integration in personal schemas of morally experiences to self-awareness of mental states : A qualitative study among a sample of Portuguese war veterans - Ferrajão, Paulo (2015)
This study explored the factors to which a sample of Portuguese war veterans attributed their recovery from posttraumatic symptoms related to their war experiences. Participants were a sample (n 60) of war veterans with mental sequelae of the Portuguese Colonial war: 30 suffered from chronic PTSD (unrecovered) and 30 veterans with remission from PTSD (recovered). Two individual semistructured interviews were conducted. Analysis of the interviews was conducted using the Thematic and Categorical Analysis. Six themes were identified to which participants attributed their recovery: war zone stressors, stressful life events, mental and coping strategies, self-integration in personal schemas of morally incongruent experiences, self-awareness of mental states, and perceived social support. Recovered participants showed higher occurrence of integration of the morally incongruent events within existing personal schemas, self-awareness of mental states, and use of problem focused coping. Unrecovered participants showed higher occurrence of lack of self-awareness of mental states, use of acting out strategies and lack of social support. The authors discussed that reconciliation of morally discrepant experiences in their self- and relational-schemas, and development of higher self-awareness of their own mental states can play a pivotal role in recovery from PTSD among war veterans.